2005
DOI: 10.1021/jp0550457
|View full text |Cite
|
Sign up to set email alerts
|

DNA Functionalized Single-Walled Carbon Nanotubes for Electrochemical Detection

Abstract: Single-walled carbon nanotubes (SWNTs) were effectively dispersed and functionalized by wrapping with single-stranded DNA (ssDNA). The ssDNA-SWNTs attach strongly on glass substrate and easily form a uniform film, making it possible for electrochemical analysis and sensing. The film was fabricated into a working electrode, which exhibited good electrochemical voltammetric properties, such as flat and wide potential window, well-defined quasi-reversible voltammetric responses, and quick electron transfer for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 31 publications
2
103
1
4
Order By: Relevance
“…Additionally, if one chooses, oligonucleotides can be removed using small aromatic molecules such as rhodamine 6G or the complementary DNA strand, once any necessary processing is complete [99] . A variety of different applications, such as fibre spinning [102] ; self-assembled nanotube field-effect transistors [103] ; stabilization of colloidal particles [104] ; chemical sensing [105] ; and both medical diagnostic and biological fields [100,[106][107][108][109] have been investigated for DNA-dispersed SWNTs.…”
Section: Biomoleculesmentioning
confidence: 99%
“…Additionally, if one chooses, oligonucleotides can be removed using small aromatic molecules such as rhodamine 6G or the complementary DNA strand, once any necessary processing is complete [99] . A variety of different applications, such as fibre spinning [102] ; self-assembled nanotube field-effect transistors [103] ; stabilization of colloidal particles [104] ; chemical sensing [105] ; and both medical diagnostic and biological fields [100,[106][107][108][109] have been investigated for DNA-dispersed SWNTs.…”
Section: Biomoleculesmentioning
confidence: 99%
“…In each case, the majority of objects have diameters below 3 nm. It has been suggested that ultracentrifugation removes all bundles from the dispersion, leaving a dispersion that contains only individual SWNTs (10,19,32,36). However, previous studies on DNA-SWNT dispersions have shown that small bundles remained in solution even after vigorous ultracentrifugation (16).…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the advantages of DNA and carbon nanomaterials, the combination of DNA and carbon nanomaterials offers unique advantages for different application. Hence, the combination of DNA with new carbon allotropes is a skillful and challenging area that can lead to the development of novel nano-biomaterials with exceptional properties for a variety of potential applications such as gas sensors and catalysts, as well as electronic and optical devices, sensitive biosensors, and biochips [46,47].…”
Section: Fullerene(c60)-dna Hybridmentioning
confidence: 99%